Importance of anticoagulant proteins in chronic liver diseases - Şebnem GÜRSOY; Mevlüt BAŞKOL; Edip TORUN; Alper YURCİ and Işın SOYUER and Bülent ESER and Kadri GÜVEN and Ömer ÖZBAKIR and Mehmet YÜCESOY (Turkish Journal of Gastroenterology, 2019)
-